Economic Education Students' Perspectives on AI Utilization in Learning: A Descriptive Study - Auna, Hariyanto S.; Polamolo, Cristian; Auna, Isnahriyati S.; Ma'ruf, Abd Rahman K.; Darojat, Achmad (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This study explores students' perspectives on the use of Artificial Intelligence (AI) in education. Using a descriptive quantitative approach, data were collected through questionnaires from 45 Economics Education students at Universitas Negeri Gorontalo. The analysis results show that 60% of respondents believe AI enhances learning efficiency, while 55.6% support its development in economic education due to its benefits for job readiness. However, concerns exist that reliance on AI may reduce critical thinking skills (62.2%) and only minimally support student collaboration (62.2%). These findings provide insights for the development of AI-based educational tools, though they are limited to a specific student group. Further research is recommended to include a larger and more diverse sample to gain a broader understanding of students' perceptions of AI in education.